2017
DOI: 10.1088/1361-6560/62/9/3422
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation-based viscosity mapping for magnetic particle imaging

Abstract: Magnetic particle imaging (MPI) has been shown to provide remarkable contrast for imaging applications such as angiography, stem cell tracking, and cancer imaging. Recently, there is growing interest in the functional imaging capabilities of MPI, where 'color MPI' techniques have explored separating different nanoparticles, which could potentially be used to distinguish nanoparticles in different states or environments. Viscosity mapping is a promising functional imaging application for MPI, as increased visco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 53 publications
2
75
0
1
Order By: Relevance
“…Using an adaption of the temperature mapping method proposed in [20] we provided the first viscosity quantification of a series of samples within a viscosity range of 1.0-51.8 mPa s with a methodological error of 6%. Thereby, extending the qualitative proof-of-concept given in [19] for a viscosity range of 0.89 mPa s to 15.33 mPa s by our quantitative results. This allows a first comparison of MPI viscosity mapping capabilities with spectroscopic methods which reported methodological errors as low as 0.1% [7] within a viscosity range of 0.96-260 mPa s. The total error of the viscosity estimation is composed of a methodological estimation error and a calibration error.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Using an adaption of the temperature mapping method proposed in [20] we provided the first viscosity quantification of a series of samples within a viscosity range of 1.0-51.8 mPa s with a methodological error of 6%. Thereby, extending the qualitative proof-of-concept given in [19] for a viscosity range of 0.89 mPa s to 15.33 mPa s by our quantitative results. This allows a first comparison of MPI viscosity mapping capabilities with spectroscopic methods which reported methodological errors as low as 0.1% [7] within a viscosity range of 0.96-260 mPa s. The total error of the viscosity estimation is composed of a methodological estimation error and a calibration error.…”
Section: Discussionsupporting
confidence: 83%
“…A different approach was proposed in [16,17] where 1D x-space MPI signals were evaluated at two drive-field strength allowing to colorize an image based on the Brown and Néel relaxation mechanisms yielding qualitative mobility information of the MPI tracer particles. Furthermore, in [18,19] a proof-ofconcept was provided that viscosity mapping can be achieved through the estimation of relaxation time constants from the two half cycles of the MPI time signal. Another technique developed in [3] generalizes the calibration based algebraic image reconstruction method to exploit the differences in the corresponding particle responses for the imaging of different particle types and aggregation states.…”
Section: Introductionmentioning
confidence: 99%
“…Correct (t edge , τ ) pair should restore the mirror symmetry, minimizing the mean squared error (MSE) between positive and mirrored negative signals after the deconvolution, i.e., (12) whereŝ(t) denotes the signal after deconvolution with the estimated relaxation kernel. Here, instead of computing MSE over the entire half period, more weights can be assigned to central time points that typically have higher SNR [31].…”
Section: A Experimental Relaxation Time Constant Estimationmentioning
confidence: 99%
“…• Upper limit on estimations: Extensive work in nanoparticle relaxometry showed that relaxation time constants are much smaller than the period of the drive field [34], typically less than 10% of the period [31]. Here, we ignore estimations that are larger than one-fourth of the period.…”
Section: B Proposed Algorithm: Calibration-free Multi-color Mpimentioning
confidence: 99%
See 1 more Smart Citation